Pengaruh Brand Image dan Content Review Terhadap Purchase Decision Smartphone Xiaomi di Kota Surabaya - Delia Noor Rizkita Kisworo; Hery Pudjoprastyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The growth of the smartphone industry encourages consumers to consider various factors before making a purchase decision. This study aims to analyze the influence of Brand Image and Content Review on Purchase Decision among Xiaomi smartphone users in Surabaya. The research employed a quantitative method with a survey approach by distributing questionnaires to 99 respondents who are consumers using Xiaomi smartphones. The data were analyzed using Partial Least Square (PLS) with the assistance of SmartPLS software to test validity, reliability, and hypotheses. The sampling technique applied was non-probability sampling with purposive sampling. The results indicate that Brand Image has a positive and significant effect on Purchase Decision. Similarly, Content Review also shows a positive and significant influence on Purchase Decision. These findings suggest that both Brand Image and Content Review contribute to influencing consumers' purchase decisions when buying Xiaomi smartphones.